Efeito da corrente interferencial na fibromialgia : ensaio clínico randomizado - Araújo, Fernanda Mendonça (2015)
Fibromyalgia (FM) is a syndrome characterized by chronic widespread musculoskeletal pain and hyperalgesia, especially in specific points called |tender points|. Furthermore, this syndrome is associated with psychosomatic disorders, such as chronic fatigue, depression, anxiety and sleep disorders. Interferential current (IFC) is a non-pharmacological and non-invasive treatment commonly used in promoting the symptomatic relief of pain. However, there is little evidence to support the effective use of IFC in patients with FM and little is known about the optimal parameters of stimulation by IFC. Thus, the present study had, as objective, to investigate the effects of different intensities of stimulation with IFC in pain relief and the other disorders present in individuals with FM. This study is a randomized, placebo-controlled and double-blind clinical trial. To assess the effects of IFC before and after treatment, the following outcomes were measured (with their respective instruments) in each session of application by IFC: pressure pain threshold (PPT: digital algometry), cutaneous sensory threshold (CST: von Frey filaments) and pain intensity at rest (11-point numeric rating scale). In addition, were also measured in the first and last day of treatment: impact of fibromyalgia (Fibromyalgia Impact Questionnaire), depression level (Beck Depression Inventory), anxiety (State-Trait Anxiety Inventory), functional capacity (Sitting-Rising and Timed Up and Go tests), fear to move (Tampa Scale of Kinesiophobia), pain catastrophizing (Pain Catastrophizing Scale), characterization of pain (McGill Pain Questionnaire), quality of life (Short Form Health Survey 36), temporal summation (temporal summation test), conditioned pain modulation (conditioned pain modulation test) and fatigue intensity (11-point numeric rating scale). Twenty nine women with FM were recruited and allocated to three groups: Motor (n=10; IFC was applied at high intensity, with motor contraction), Sensory (n=10; high intensity, but without motor contraction) and placebo (n=9). Patients allocated into the motor and sensory groups were stimulated at an amplitude-modulated frequency of 100 Hz, for 30 minutes. In the placebo group, the current was released only in the first 40 seconds of stimulation. Ten treatment sessions were performed and the electrodes were applied to the paravertebral region. The t Student test, Wilcoxon and ANOVA for repeated measures were used to compare the results found, intra-group, before and after treatment. In women allocated to the motor group, there was a significant increase PPT, measured in the conditioned pain modulation test (p≤0.03), and significant reduction in amplification of pain intensity in temporal summation (p=0.03) after the end of treatment. None of the studied group showed significant change in the PPT and CST values in 18 tender points specific to FM, and pain intensity each treatment session with IFC (p>0.05). However, only the motor group had a significant reduction in the impact of the disease (p=0.01), depression (p=0.006), anxiety state (p=0.01), kinesiophobia (p=0.002), catastrophizing (p=0.008), pain rating index (p=0.04), fatigue (p=0.02) and number of tender points (p=0.04), and increased quality of life (p=0.006). Thus, the results, obtained in this study, provide strong evidence that the IFC, only when applied in high intensities of stimulation, is an effective treatment in reducing pain and psychosomatic disorders present in patients with FM